Adult Learner perceptions and experiences in a Community College engaged in intensive student success reforms - Susan J Barcinas; Tracy A Kachur; Duane Akroyd; Heidi N McCann; Yaxin Zheng (Adult Education Research Conference, 2016)
This qualitative study is based upon 200 hours of observation and 30 participant interviews aiming to deeply describe and analyze adult learner perceptions of community college intensive student success reform initiatives.
Keywords: adult learners; community colleges; qualitative; student success